Generalized Iterated Function Systems Containing Functions of Integral Type - S, Minirani; ., . (International Journal of Engineering and Technology, 2018)
A finite collection of mappings which are contractions on a complete metric space constitutes an iterated function system. In this paper we study the generalized iterated function system which contain generalized contractions of integral type from the product space . We prove the existence and uniqueness of the fixed point of such an iterated function system which is also known as its attractor.Â